Mnogoletnyaya dinamika sportivnogo masterstva v ryvke i tolchke u sil'neishikh tyazheloatletok mira - Medvedev, A. S. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this study was to analyse the peculiarities of the world elite women weight lifters' sports mastery dynamics. The sports results of the first six positions in each weight category achieved by elite women weight lifters at eight world championships and ten China Championships from 1985 to 1994. The obtained data had allowed to conclude that the tempos of the result's progress in Chinese women weight lifters were higher than in Russian ones. The author considers that one of the most important factors influencing on the dynamics of sports mastery's improvement in Chinese and Russian women athletes are the age of the sports training beginning, the time of sports training and the practice of going for other kinds of sport before weight lifting training.